Pemberian Kue Kering Tepung Ubi Jalar Ungu DenganTepung Tempe Terhadap Gula Darah Sewaktu Pada Penderita Diabetes Mellitus Type 2 Di Rumah Sakit dr. Tadjuddin Chalid Makassar - Nurhayati Muslimin; Lydia Fanny; Manjilala Manjilala (Media Gizi Pangan, 2018)
Diabetes Mellitus (DM) is a collection of symptoms that arise in someone who has increased blood sugar levels (Glucose) due to lack of insulin hormone. The content in purple and tempe sweet potatoes has high amylose fiber content, and low IG improves insulin sensitivity, decreases glucose uptake rate, and is useful in controlling blood glucose so as to reduce the risk of complications in people with diabetes mellitus type 2 .This study aims to determine the effect of pastry cake flour sweet potato purple and tempe powder to blood sugar levels in patients with diabetes mellitus Type 2 in dr. Tajuddin Chalid Makassar.This study is an analytical study with Pre-Experiments by looking at blood glucose levels in the subjects who suffer from diabetes mellitus type 2 with the number of samples senbanyak 12 respondents. The result of data analysis of the effect of sweet potato pie cake and tempe powder to Diabetes Mellitus Type 2 patients was analyzed using SPSS with Wilcoxon test. The presentation of data is presented in tabular and narrative form.The results show Asymp.Sig (2-tailed) is 0.005. Because Asymp.Sig (2-tailed) is worth 0.005 which means There is effect of cake pastry sweet potato purple powder and tempe powder to blood sugar while in patient of Diabetes Mellitus Type 2 in dr. Tadjuddin Chalid Makassar.It is advisable to control blood sugar regularly at least once a month, physical exercise such as doing regular physical activity at least 3 times a week, and multiply the activities at home. Should counseling about Diabetes Mellitus type 2 Related to the recommended foodstuffs and is not recommended for people with Diabetes Mellitus (DM) type 2.